2011
DOI: 10.1002/jmor.11034
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in morphology of vertebral centra and intervertebral joints in striped bass, Morone saxatilis

Abstract: The vertebral column of fishes has traditionally been divided into just two distinct regions, abdominal and caudal. Recently, however, developmental, morphological, and mechanical investigations have brought this traditional regionalization scheme into question. Alternative regionalization schema advocate the division of the abdominal vertebrae into cervical, abdominal, and in some cases, transitional regions. Here, we investigate regional variation at the level of the vertebrae and intervertebral joint (IVJ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 35 publications
7
41
3
Order By: Relevance
“…In contrast to these findings of constant or increasing IVJ stiffness from cranial to caudal, a recent morphological study predicted decreasing flexural stiffness and increasing ROM from cranial to caudal in striped bass, M. saxatilis [19]. The study found a longitudinal variation in the soft tissues of the IVJ; the volume of the notochordal cell mass and the cross-sectional area of the helically wound fibrous sheath both decreased from cranial to caudal, and regional variation was found in the number of fibre populations and the insertion angle of those populations in the vertical septum.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In contrast to these findings of constant or increasing IVJ stiffness from cranial to caudal, a recent morphological study predicted decreasing flexural stiffness and increasing ROM from cranial to caudal in striped bass, M. saxatilis [19]. The study found a longitudinal variation in the soft tissues of the IVJ; the volume of the notochordal cell mass and the cross-sectional area of the helically wound fibrous sheath both decreased from cranial to caudal, and regional variation was found in the number of fibre populations and the insertion angle of those populations in the vertical septum.…”
Section: Introductionmentioning
confidence: 77%
“…Estimates of the second moment of area for the IVJs along the length of the fish predicted a lower stiffness in the most rostral and caudal regions, relative to the abdominal (middle) joints. Thus, on the basis of the soft-tissue morphology and geometry of vertebrae and IVJs, this study predicted an increase in ROM from cranial to caudal and a lower stiffness in the caudal than in the abdominal IVJs [19].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations